Design for high-quality factor of piezoelectric-on-silicon MEMS resonators using resonant plate shape and phononic crystals. (16th March 2021) - Workie, Temesgen Bailie; Wu, Ting; Bao, Jing-Fu; Hashimoto, Ken-ya
Abstract: Piezoelectric-on-silicon MEMS resonator is very well known for its compatibility with CMOS integrated circuit technology. However, its quality factor ( Q ) is highly affected by acoustic energy loss through the supporting structures. In this study, a resonator with butterfly-like round edge resonating plate structure and deploying properly designed PnC arrays on the tether and the anchoring boundaries are proposed to scale up the quality factor by effectively reducing the energy loss. The finite element analysis simulation results reveal that the proposed topologies can efficiently change the displacement field in the resonating plate and reduce the anchor loss. Consequently, an unloaded quality factor Q u of the conventional resonator is raised from 29 899 to 51 503 (butterfly-like round edge resonating structure), 83 349 (Phononic crystal on the tether) and 83 899 (Phononic crystal on the anchor), representing 1.7 folds, 2.78 folds and 2.8 folds improvement respectively.